2014
DOI: 10.1037/pas0000017
|View full text |Cite
|
Sign up to set email alerts
|

The clinical utility of the MMPI–2–RF Suicidal/Death Ideation Scale.

Abstract: Suicide is a major public health concern with over 100 individuals dying by suicide per day in the United States alone. Therefore, suicide risk assessment is an essential aspect of mental health care. The MMPI-2-RF has a Suicidal/Death Ideation (SUI) scale consisting of 5 items that describe recent suicidal ideation or behaviors. Although this scale has clear face validity, few studies have examined the clinical utility of this scale. The purpose of the current study was to examine associations between the SUI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 35 publications
5
29
0
Order By: Relevance
“…That being said, prior studies have reported that these two measures, even when scored continuously, correspond extremely highly with one another. Indeed, whereas the two measures were only modestly correlated with one another in our sample (r = .48), prior work has indicated that the two exhibit a nearly perfect correlation with one another (r = .90; Gottfried et al, 2014). Given these vastly discrepant findings across samples, we believe that the more parsimonious interpretation is that soldiers in our sample responded differently to each measure because of the differential incentives in place, given the varying levels of confidentiality associated with each measure.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…That being said, prior studies have reported that these two measures, even when scored continuously, correspond extremely highly with one another. Indeed, whereas the two measures were only modestly correlated with one another in our sample (r = .48), prior work has indicated that the two exhibit a nearly perfect correlation with one another (r = .90; Gottfried et al, 2014). Given these vastly discrepant findings across samples, we believe that the more parsimonious interpretation is that soldiers in our sample responded differently to each measure because of the differential incentives in place, given the varying levels of confidentiality associated with each measure.…”
Section: Discussionmentioning
confidence: 62%
“…As such, concerns that our two measures of current suicidal thoughts are assessing different constructs are warranted if the measures are scored continuously; however, when dichotomized, we can reasonably assume that the two measures assess the presence and absence of suicidal thoughts, with some individuals endorsing more severe, persistent, and detailed thoughts than others. It should also be noted that, in other studies, the DSI-SS and BSS have correlated at such high levels (r = .90) that an argument could be made that they assess the same construct even when scored continuously (Gottfried, Bodell, Carbonell, & Joiner, 2014). The alpha coefficient for the participants included in our analyses was .81.…”
Section: Methodsmentioning
confidence: 66%
See 1 more Smart Citation
“…The functioning reflected in T-scores. A T-score of 65 or higher interpreted as a score in clinical range (17). The reliability coefficient of scales for main test are 0.70 and 0.80 with split method.…”
Section: Minnesota Multiphasic Personality Inventory (Mmpi -2)mentioning
confidence: 99%
“…The validity scales consistently discriminate between valid and invalid patterns of responding (Goodwin et al 2013;Nelson et al 2011;Sellbom et al 2012b;Shura et al 2017), offering a means to evaluate the potential for response bias within the VA (Ray 2017). Similarly, the substantive scales are useful in predicting diagnostic presentations and identifying important clinical concerns (Koffel et al 2012;Gottfried et al 2014;Sellbom et al 2012a;Wolf et al 2008). Moreover, the substantive scales have also been shown to predict treatment engagement (Anestis et al 2015;Arbisi et al 2013) and other treatment outcomes (Arbisi et al 2008;Forbey et al 2012).…”
mentioning
confidence: 98%